Sample preparation in biological mass spectrometry lexander R. Ivanov, Alexander V. Lazarev, editors. - Ivanov, Alexander R.; Lazarev, Alexander; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
The Goal and philosophy of sample preparation in biological mass spectrometry is to reveal the actual multicomponent molecular structure of a biological specimen that can be assessed by mass spectrometry tools. Unfortunately, sample preparation is often looked at as a necessary but ?boring? step which does not warrant any efforts beyond a paragraph or two in a "Methods" section; it is believed not to be conducive to innovation, and does not elicit the enthusiasm of funding agencies. Nevertheless, in recent years, the attention to sample preparation methods has risen considerably, both in Academia and in the life science industry. The aim of this book is to provide the researcher with important sample preparation strategies for a wide variety of analyte molecules, specimens, methods, and biological applications demanding mass spectrometric analysis as the detection end-point. In this volume we have compiled contributions from several laboratories that employ mass spectrometry for biological analysis. With the latest inventions and the introduction of highly sophisticated mass spectrometry equipment, sample preparation has become an extremely important bottleneck of biomedical analysis. This book is structured as a compilation of contributed chapters ranging from step-by-step protocols to research articles and reviews. The main philosophy of this volume is that sample preparation methods have to be optimized and validated for every project, for every sample type and for every downstream analytical technique.
Introduction: Sample Preparation ? Boring but Important! Section I. Traditional and improved techniques in sample preparation for proteomics -- Section II. Methods for Improved Proteolytic Digestion -- Section III. Methods for Tissue, Cell, and Organelle Preparation and Analysis -- Section IV. 2D Gel-based Proteomics -- Section V. Sample Preparation and Analysis Techniques for Biological Fluids and Biomarker Discovery.- Section VI. Sample Preparation Methods in Plant Proteomics Section -- VII. Affinity Interaction and Biochemical Enrichment Techniques -- Section VIII. Methods for Quantitative proteomics -- Section IX. Sample Preparation in Functional Proteomics -- Section X. Characterization of Membrane Proteins.- Section XI. Methods for MALDI MS Enabled Biomedical Applications.- Section XII. Clinical Research and Applications.- Section XIII. Sample Preparation Techniques in Metabolomics and Drug Discovery -- Section XIV. Sample Preparation in Analysis or Exotic and Limited Availability Specimens -- Section XV. Sample Treatment in Biodefense, Forensics and Infectious Diseases -- Section XVI. Novel Approaches in Sample Preparation and LC-MS Analysis.
Electronic reproduction.
Keywords: Sample preparation (Chemistry).; Mass spectrometry; Electronic books